Analisis Komunikasi Pemasaran Terpadu PT. Laxo Global Akses Dalam Membangun Brand Association - R. Satria Setyanugraha (FEB Universitas Sultan Ageng Tirtayasa, 2021)
PT. Laxo Global Akses, which is better known as LAXO, is an Internet Service Provider (ISP) that has an official license to operate nationally in Indonesia. LAXO is also registered as an active member of APJII (Indonesian Internet Service Providers Association). Internet services provided by LAXO include all internet services such as network installation, browsing, email, streaming (video / voice), hotspots, VPN (Virtual Private Network), conference meetings, CCTV (closed circuit television), Online Live, and VoIP ( InternetProtocol Voice offer). This study discusses the Integrated Marketing Communication (IMC) carried out by LAXO to build the brand image of the company. The author takes this topic because the author thinks that LAXO is a new ISP company, but already has quite a lot of client references and comes from large companies. Even though competition in the ISP world is not easy, because the main competitors are BUMN. Keywords: marketing; communication; LAXO; Internet; brand.